The Enchantment of Lampung Banana Chips: Captivating The Global Palate with Unique Indonesian Flavours - Mey Ayu Lestari; Desriani Hadi; Claranesia Zenita Putri; Alvis Oktanza Fayardi; Rindu Rika Gamayuni (Akuntansi, 2025)
Lampung banana chips have great potential to compete globally due to their distinctive sweet and savory taste. However, the introduction of this product is still limited, so efforts are needed to expand its reach in the international market. During the Field Study Problematic Seminar on Global Accounting at Ryukoku University, Japan, held on October 17, 2024, an introduction to Lampung banana chips was made by distributing brochures and product samples to students. This International Community Service (PKM) activity aims to increase the attractiveness of Lampung banana chips in the global market by introducing its taste to Ryukoku University students. This activity is expected to provide an understanding of international consumer preferences as a first step in encouraging product innovation to suit global market tastes better. These innovations include the development of new flavors, improved packaging quality, and more effective marketing strategies to attract global consumers. The expected result of this activity is the increased awareness and understanding of Ryukoku students towards Indonesian food, especially Lampung banana chips, and the emergence of a unique attraction for this product in the global market. By understanding the tastes of international consumers, it is hoped that in the future, more strategic product development can be carried out so that Lampung banana chips will be more competitive in the international market and be able to compete with similar products from other countries.